Non-occupational lead poisoning associated with traditional Chinese medicine: A case report - Huan Ma; Li-meng Wu; Yu Zou; Xiao-an Li (Frontiers Media S.A., 2022)
IntroductionTraditional Chinese medicine has a long history and is widely popular in China because of its safety and small side effects. In Chinese families, people believe that the combination of traditional Chinese and Western medicine is more effective, and in terms of conditioning and health care, they tend to rely on traditional Chinese medicine. However, the toxic and side effects of traditional Chinese medicine, especially heavy metal poisoning, should not be ignored.Patient concernsA case of non-occupational lead poisoning caused by long-term use of traditional Chinese medicine.DiagnosisA 21-year-old man with severe colic periumbilical pain was referred to our hospital. Through careful inquiry of his medical history, we found that he had been taking traditional Chinese medicine to treat facial acne in the past year. His test results showed anemia, liver damage, blood lead concentration of 1,268.4 μg/L, and bone marrow smear showed basophilic stippling erythrocyte. The patient was diagnosed with "lead poisoning."InterventionsThe patient was given treatment with lead driving.OutcomesThe patient recovered after treatment.ConclusionWe found that lead poisoning in patients taking traditional Chinese medicine has been reported from time to time. Through consulting the data, we summarized the most common drugs leading to lead poisoning, and reviewed the pathogenesis and common clinical manifestations of lead poisoning. Because lead poisoning is easy to be misdiagnosed, we should ask more carefully about the past history and drug history of patients in order to make timely diagnosis and treatment.